EFFECTIVENESS OF BIOSTIMULANTS IN IMPROVING GERMINATION, GERMINATION ENERGY AND INCREASING SOYBEAN BIOMASS - Ласло, Оксана; Кожушко, Катерина (SWorldJournal, 2025)
The article highlights the results of a study of the effect of biostimulants Grand, Grand Alitti, and Grand Ermei on germination energy, laboratory germination, and soybean biomass growth under laboratory conditions. The aim of the study was to establish